Page Kidney Phenomenon following Kidney Graft Biopsy - Jackie Mak; Bulang He (Journal of Surgery and Surgical Research - Peertechz Publications, 2018)
Percutaneous renal allograft biopsy is commonly performed as a protocol or diagnostic biopsy after kidney transplantation to detect rejection, recurrence of kidney disease, infection and calcineurin inhibitor (CNI) nephrotoxicity [1,2]. It is generally considered as a safe procedure under ultrasound guidance. However, some complications associated with this procedure can occur. Most common complications are minor and can be managed conservatively. Major complications can occur in about 1% of cases [3,4], which may require blood transfusion, interventional procedure or even surgical exploration. Page kidney phenomenon is one of the rare but serious complications, in which the renal parenchyma is tamponade and its perfusion is compromised as a result of haematoma formation under the renal capsule. This will lead to deterioration in kidney function and graft loss if the diagnosis and management are delayed [5]. Therefore, early recognition of page kidney phenomenon is crucial as prompt evacuation of the haematoma can prevent graft loss and allow complete recovery of renal function [6]. Here we reported two cases of page phenomenon after kidney graft biopsy in our institution. The literatures were also reviewed.